Thermodynamic and economical analysis of organic rankine cycle usage with natural gas fired internal combustion engine waste heat - Talu, Yunus Emre (My University, 2019)
Nowadays, heat recovery systems are coming into substantially prominence in conjunction with augmentation of pollution allied with fossil fuel dependency and population growth. Internal combustions engines are one of primarily responsible about fossil fuel consumption with widely utilization area beside all benefits to humanity such as transportation, power unit and agricultural machinery. In this study, Organic Rankine Cycle (ORC) usage analyzed as a heat recovery system for exhaust gas heat loss of Internal Combustion Engine (ICE) which is TCG2032 model manufactured by MWM brand of Caterpillar Energy Solutions GmbH. Mathematical models were developed for two different chosen cycles which are basic ORC and regenerative ORC in conscious the simplicity and lower investment cost necessity of a heat recovery system. Regenerative cycle includes an additional internal heat exchanger distinctly from basic cycle for the purpose of maximize cycle efficiency via provide pre-heat with cycle waste heat. Seven different working fluids that R113, R123, R134a, R141b, R245fa, n-xii pentane and n-butane were taking in consideration for both basic and regenerative cycle to represent different fundamental classes of fluids which are isentropic, dry and wet type. The maximum net power output was selected as the foremost evaluation criterion to analyze heat recovery system effectiveness. Optimization study importance is ensuing with the different working condition necessities for maximize net output power of working fluids relative to different thermal and physical characteristics. Maximum net output power of cycle was defined depending on different heat source conditions by help of optimization study which was made with the results of the first law and second law efficiency of each fluid and cycle combination. The thermal analysis results reveal that the R113 is the most efficient working fluid for regenerative cycle and R141b is the most efficient working fluid for basic cycle. R134a is one of the wet type fluids and it has the lowest net output power as comparatively from the other selected fluids. Generally, regenerative cycle produce more power than basic cycle with the rate of between 30-50%. Also analyzes show that the 6-17% increase at the overall efficiency appear possible with ICE-ORC combined cycle in according to single engine, and as a result of that 400-1000 kW reduce can be achieved for the fuel energy consumption. Besides that, Regenerative ORC was found more profitable with the 8,46 years Payback Period (PBP) against Basic ORC which has 9,82 years PBP.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2019
Keywords: Organic rankine cyd; Heat recovery system; Engine waste heat recovery; Economic analysis; Optimization study